Psikososial Berkendara Agresif - Swari, Made Ardha Nare (Universitas Muslim Maros, 2024)
Traffic accidents pose a serious threat to modern society, with significant consequences including injury, disability, death, and economic and social impacts, caused primarily by motor vehicles, and influenced by environmental, mechanical, and human factors. Current traffic research often focuses on driver-related factors, including aggressive driving behavior. This article aimed to review literature concerning aggressive driving and the psychosocial factors that may influence it. This article is based on an examination literature review of 18 research articles, regarding psychological variables influencing aggressive driving behaviour. The study shows that psychosocial factors are categorised into four, namely cognitive, personality, mental condition, and social factors. Cognitive factors consist of risk perception, self-control, moral disengagement, perceived behavioral control, traffic locus of control, mindfulness, psychological resilience, cognitive reappraisal, cognitive emotion regulation, and difficulties in emotion regulation. Personality factors comprise the Big Five traits (conscientiousness, agreeableness, and neuroticism), the Dark Triad traits (narcissism, Machiavellianism, and psychopathy), the Light Triad traits (humanism, Kantianism, and faith in humanity), life history strategies, driver overconfidence, attitudes toward aggressive driving, willingness to drive aggressively, emotional maturity, emotional intelligence, impulsivity, and sensation seeking. Mental condition factors consist of stress, anxiety, and depression. Social factors consist of social desirability, safe driving climate among friends (peer pressure, social costs, communication, and shared commitment to safe driving), social exclusion, social identity, and masculinity. This literature review is constrained by the limited number of sources analyzed. Future research should aim to include a greater number of studies and broaden the scope of psychosocial factors influencing aggressive driving.